Geometric aspects of analysis and mechanics in honor of the 65th birthday of Hans Duistermaat - Ban, Erik P. van den; Kolk, Johan A. C. 1947-; SpringerLink (Online service). (Boston, Massachusetts Birkhäuser Boston, 2011)
Hans Duistermaat, an influential geometer-analyst, made substantial contributions to the theory of ordinary and partial differential equations, symplectic, differential, and algebraic geometry, minimal surfaces, semisimple Lie groups, mechanics, mathematical physics, and related fields. Written in his honor, the invited and refereed articles in this volume contain important new results as well as surveys in some of these areas, clearly demonstrating the impact of Duistermaat's research and, in addition, exhibiting interrelationships among many of the topics.

Contributors include J.-M. Bismut, L. Boutet de Monvel, Y. Colin de Verdière, R.H. Cushman, N. Dencker, F.A. Grünbaum, V.W. Guillemin, J.-C. Hausmann, G. Heckman, T. Holm, L.C. Jeffrey, F. Kirwan, E. Leichtnam, B. McLellan, E. Meinrenken, P.-E. Paradan, J. Sjöstrand, X. Tang, S. Vũ Ngọc, A. Weinstein.
Preface -- About J.J. Duistermaat -- Hans Duistermaat (1942-2010) -- Recollections of Hans Duistermaat -- Recollections of Hans Duistermaat -- Recollections of Hans Duistermaat -- Classical Mechanics and Hans Duistermaat -- Duistermaat-Heckman formulas and index theory -- Asymptotic equivariant index of Toeplitz operators and relative index of CR structures -- A semi-classical inverse problem I: Taylor expansions -- A semi-classical inverse problem II: reconstruction of the potential -- On the solvability of systems of pseudodifferential operators -- The Darboux process and a noncommutative bispectral problem: some explorations and challenges -- Conjugation spaces and edges of compatible torus actions -- Non-Abelian localization for U(1) Chern-Simons theory -- Symplectic implosion and non-reductive quotients -- Quantization of q-Hamiltonian SU(2)-spaces -- Wall-crossing formulas in Hamiltonian geometry -- Eigenvalue distributions and Weyl laws for semi-classical non-self-adjoint operators in 2 dimensions -- Symplectic inverse spectral theory for pseudodifferential operators.
Electronic reproduction.
Keywords: Geometric analysis; Operator theory; Mathematical analysis